Definitional Challenges in Understanding Hypertrophic Cardiomyopathy - Jan M. Federspiel; Jochen Pfeifer; Frank Ramsthaler; Jan-Christian Reil; Peter H. Schmidt; Vasco Sequeira (Diagnostics)
Hypertrophic cardiomyopathy (HCM) is the most common hereditary cardiomyopathy. It is often caused by mutations of genes encoding for sarcomeric or sarcomere-associated proteins. Despite its clinical importance, divergent definitions are published by major cardiology societies. Some regard HCM as a specific genetic disease, whereas others define it as a broad ‘spectrum of the thick heart’. The present narrative review aimed to assess both definitions from a pathoanatomical perspective. As a conjoint interdisciplinary and translational approach is needed to further increase knowledge and improve the understanding of HCM, the PubMed database was searched using several advanced search algorithms to explore the perspectives of the (forensic) pathologist, clinician, and basic researcher regarding the difference between the definitions of HCM. This discrepancy between definitions can impact critical data, such as prevalence and mortality rate, and complicate the understanding of the disease. For example, due to the different definitions, research findings regarding molecular changes from studies applying the narrow definition cannot be simply extended to the ‘spectrum’ of HCM.